2020
DOI: 10.1016/j.jcte.2019.100207
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ disease and mental disorders

Abstract: Mental disorders merge highly with thyroid diseases. Because of its regulatory effects on serotonin and noradrenalin, T3 has been linked closely to depression and anxiety. It has known that in many cases, the mental symptoms persist even after normalization of thyroid function by treatment. Psychosocial factors including stress have been associated with mental symptoms even after thyroid function normalization in Graves’ disease and a combination of mental disorders have been related to the exacerbation of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 53 publications
(54 reference statements)
1
33
1
4
Order By: Relevance
“…In the present study, anxiety and depression were more frequent in the group of patients with Graves’ disease than in the healthy population, which is consistent with the literature [ 5 , 12 ]. More than half of our patient group had anxiety (55%) and nearly half of the same group had depression (42.5%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, anxiety and depression were more frequent in the group of patients with Graves’ disease than in the healthy population, which is consistent with the literature [ 5 , 12 ]. More than half of our patient group had anxiety (55%) and nearly half of the same group had depression (42.5%).…”
Section: Discussionsupporting
confidence: 93%
“…Changes in the levels of neurotransmitters such as dopamine, which is associated with motivation; noradrenaline, which is associated with attention, concentration, and wakefulness; and serotonin, which is associated with mood, sleep, nutrition, and aggression may affect several neuropsychiatric functions, especially cognitive functions, thus leading to cognitive-behavioral pathologies in individuals with thyroid disease [ 4 ]. Therefore, these patients may easily get angry and exhibit mental pathologies such as irritability, anxiety, impulsiveness, emotional instability, inattention, inability to concentrate, sleeplessness, restlessness, and distractibility [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the dysfunction of thyroid hormone regulation causes diseases that affect the mental capacity and brain organically through the hypothalamic-pituitary axis and monoamine dysregulation, it has been shown that symptoms of mental disorders like depression persist long afterwards the treatment of the underlying disease. An occurrence of 31 and 56 percent has been observed in hyperthyroidism and hypothyroidism respectively [ 19 ]. We found that 40% of our patients with underlying thyroid disease were affected with moderate to severe forms of depression and 20% had suicidal ideation (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that 40% of our patients with underlying thyroid disease were affected with moderate to severe forms of depression and 20% had suicidal ideation (Figure 2 ). The use of novel antidepressants like SSRIs and serotonin-norepinephrine reuptake inhibitors has shown good efficacy in treating depression related to thyroid disease [ 19 ]. It is important to mention the contraindication of tricyclic antidepressants in hyperthyroid disorders which can worsen the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation